2018
DOI: 10.1136/flgastro-2017-100924
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated liver disease: a curriculum-based review

Abstract: Pregnancy is associated with changes in normal physiology, including changes to the normal parameters for blood tests. Abnormal liver function tests are a common reason for referral to gastroenterology. However, in the pregnant patient, there are unique potential causes. It is of prime importance to be aware of pregnancy-specific liver diseases as they can be serious and progress rapidly affecting outcomes for both the mother and fetus. Here, we provide an overview of the manifestations of pregnancy-related li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…As a result, most authors don't consider it a liver disease per se [12]. Studies have shown that derangement in LFT occurs in half of the patients with HG, and the biochemical abnormalities resolve on cessation of vomiting [17]. The findings of our study are in agreement with the data available.…”
Section: Discussionsupporting
confidence: 88%
“…As a result, most authors don't consider it a liver disease per se [12]. Studies have shown that derangement in LFT occurs in half of the patients with HG, and the biochemical abnormalities resolve on cessation of vomiting [17]. The findings of our study are in agreement with the data available.…”
Section: Discussionsupporting
confidence: 88%
“…Intrahepatic cholestasis of pregnancy affects 0.1-2% of pregnant women; in 1-4 women, gestation can be complicated by premature birth, fetal asphyxia, meconium staining of amniotic fluid, and stillbirth. The results of a large Swedish cohort study showed that pregnancy, in which the concentration of bile acid in maternal serum is 40 μmol/L or more, can be complicated by spontaneous preterm delivery 23 , the presence of meconium in the amniotic fluid and fetal asphyxia. Another UK cohort study confirms these findings and showed that pregnancy outcomes 22 in women with intrahepatic cholestasis in pregnant women and a serum bile acid concentration of 40 μmol/L or more often lead to fetal death compared to 2205 women with uncomplicated pregnancy 25 .…”
Section: Kremer Et Almentioning
confidence: 99%
“…In mild cases of preeclampsia, there is a mild elevation of serum AST/ALT/Alkaline phosphatase. During HELLP syndrome, serum aminotransferases are more than ten times elevated, and unconjugated hyperbilirubinemia may be present due to hemolysis (Kelly, 2018).…”
Section: Biological Evaluation Of the Thyroid The Liver The Kidneysmentioning
confidence: 99%